2021
DOI: 10.1302/0301-620x.103b7.bjj-2020-2582.r1
|View full text |Cite
|
Sign up to set email alerts
|

The association between surgical fixation of hip fractures within 24 hours and mortality

Abstract: Aims The aim of this study was to assess the effect of time to surgical intervention from admission on mortality and morbidity for patients with hip fractures. Methods MEDLINE and Embase were searched from inception to June 2020. Reference lists were manually assessed to identify additional papers. Primary comparative research studies that recruited patients aged over 60 years, with non-pathological primary proximal femoral fractures that were treated surgically, were included. Studies that did not include a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…The in-hospital mortality in the present study agrees with the risk about 2% reported currently [20], and female gender was not a significant predictor, while female was significant in the cohort by Forni et al [20]. A recent meta-analysis [21] indicated reduced mortality for patients operated within 24 h compared with those operated within 36 h. Contrary, other recent study [22]) reported that early surgery within 48 and 72 h was significantly associated with a lower in-hospital mortality in patients older than 85 years. In a prior study [23], we found that patients with severe active comorbidities could benefit from surgery delayed more than 2 days.…”
Section: Discussionsupporting
confidence: 89%
“…The in-hospital mortality in the present study agrees with the risk about 2% reported currently [20], and female gender was not a significant predictor, while female was significant in the cohort by Forni et al [20]. A recent meta-analysis [21] indicated reduced mortality for patients operated within 24 h compared with those operated within 36 h. Contrary, other recent study [22]) reported that early surgery within 48 and 72 h was significantly associated with a lower in-hospital mortality in patients older than 85 years. In a prior study [23], we found that patients with severe active comorbidities could benefit from surgery delayed more than 2 days.…”
Section: Discussionsupporting
confidence: 89%
“…Most studies set the goal of early surgery within 48 h from admission, supported by highly significant associations with lower mortality rate at different end-points [2, 4, 8, 19, 23, 24, 31-34, 38, 39]. However, some studies identify the threshold at 24 h to be significantly related to better outcome, both at short and mid-term [4,[19][20][21][22][23][24][25][26][27][28][29][30]40]. Conversely, some studies set 72 h as the limit for early surgery, with more conflicting results [8,24,33].…”
Section: Discussionmentioning
confidence: 99%
“…The influence of surgical delay on postoperative prognosis was deleterious. Mortality significantly increased for patients receiving hip repair surgery >24 hours after admission compared with those operated on within 24 hours [11]. A surgical delay of >21 days had a significantly poorer hip function and QoL than an operation within 7 days of the fracture [12].…”
Section: Introductionmentioning
confidence: 99%